A new steroid from the Red Sea soft coral Lobophytum lobophytum. Issue 3 (1st February 2016) - Hegazy, Mohamed-Elamir F.; Mohamed, Tarik A.; Elshamy, Abdelsamed I.; Hassanien, Abuzeid A.; Abdel-Azim, Nahla S.; Shreadah, Mohamed A.; Abdelgawad, Ibrahim I.; Elkady, Eman M.; Paré, Paul W.
Abstract : Chemical investigation of the soft coral Lobophytum lobophytum collected from the Red Sea led to the isolation of a new compound gorgostan-5, 25-dien-3β-ol (1 ), and two known compounds gorgosterol (2 ), and alismol (3 ). Structures were elucidated by employing extensive NMR and HR-ESI-MS experiments. Abstract :